Philippine Laws on Transfer Taxes Business Taxes : (Per the NATIONAL INTERNAL REVENUE CODE) - Litonjua, Virgilio G.; Litonjua, Lilian M. ([place of publication not identified] : Center for Training & Development Inc., 2005)
The scope of this books centers on the conceptual / theoritical the as well as on the practical application of the laws on transfer taxes and business taxes, incorporating therin the latest and relevant amendments and new impositions on said taxes as per Republic Act No. 8424 and other various Republic Acts, BIR regulations and rulings, in line with the Comprehensive Tax reform progrma, effective in the year 1998 anf thereafter.
Chapter 1 : General principles of taxation -- Chapter 2 : Administrative provisions on donors tax -- Chapter 3 : Fundamental concepts on donor tax -- Chapter 4 : Donors tax rates, tax due, taxable net gift -- Chapter 5 : Donors tax returns, donors tax credits -- Chapter 6 : Gross gift, exclusions and inclusions -- Chapter 7 : Allowed deductions, exclusions and inclusions -- Chapter 8 : Administrative provisions on estate tax -- Chapter 9 : Fundamental concepts on estate tax -- Chapter 10 : Estate tax rates, tax due, taxable net estate -- Chapter 11 : Estate tax returns, tax credits -- Chapter 12 : Gross estate, exclusions and inclusions -- Chapter 13 ; Allowed deductions, exclusions/inclusions -- Chapter 14 : Administrative provisions on percentage taxes -- Chapter 15 : Fundamental concepts on percentage tax -- Chapter 16 : Percentage tax sections ; 116 to 121 -- Chapter 17 : Percentage tax in sections : 122 to 127 -- Chapter 18 : Percentage tax returns, tax credits -- Chapter 19 : Administrative provisions value added tax -- Chapter 20 : Fundamental concepts on value added tax -- Chapter 21 : Transactions/sales ; vat exempt, zero rated, -- Chapter 22 : Value added tax on sellers goods and sellers -- Chaper 23 : Value added tax on importers of goods -- Chapter 24 : Value added tax returns, tax credits -- Chapter 25 : General rpovision on excise taxes -- Chapter 26 : Excise taxes on manufactures goods or imported goods -- Chapter 27 : Community tax
Keywords: TAXATION